2016
DOI: 10.1016/j.evolhumbehav.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized behavior increases assessments of the formidability and cohesion of coalitions

Abstract: Synchronized behavior is a common feature of martial drills and military parades in many societies. Hagen and colleagues Hagen & Hammerstein, 2009) hypothesized that the intentional enactment of synchronized behavior evolved as a means of signaling coalitional strength, as individuals who can synchronize are able to act in concert in agonistic contexts. Previous research has explored either the subjective consequences of synchrony for participants in synchronized behaviors or the effect of synchrony on observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 75 publications
(85 reference statements)
4
61
0
1
Order By: Relevance
“…If you fail at getting your group together when the enemy group comes over the hill, you are dead. Second, in group-based conflict, coordination is in itself a source 6 of greater fighting ability (21,24,25) and, hence, group-based conflict essentially is an arm's race of coordination. Many other problems of collective action require the group to meet some absolute threshold of coordination.…”
Section: The Coordination Problemmentioning
confidence: 99%
“…If you fail at getting your group together when the enemy group comes over the hill, you are dead. Second, in group-based conflict, coordination is in itself a source 6 of greater fighting ability (21,24,25) and, hence, group-based conflict essentially is an arm's race of coordination. Many other problems of collective action require the group to meet some absolute threshold of coordination.…”
Section: The Coordination Problemmentioning
confidence: 99%
“…When engaging in chorused activities, all-male bands of several species appear to be able to attract females to their group due to the quality of the display (e.g. Fessler & Holbrook 2016). It would therefore seem logical that group members who are particularly capable or competent should be sought out so as to enhance the quality of chorusing bouts.…”
Section: Synchronisation and Social Bondingmentioning
confidence: 99%
“…Hitherto, it is only possible to speculate on the extent to which this capacity has been consciously used to promote and assess cohesion throughout history, but one recent study has shown that people moving in synchrony are perceived as more formidable (e.g. Fessler & Holbrook 2016).…”
Section: Synchronisation and Social Bondingmentioning
confidence: 99%
“…Synchrony is a striking feature of male alliance behavior and may be used to advertise alliance relationships, increase the perceived formidability of allies, and help establish and maintain social bonds (Connor, 2007; Connor, Smolker, & Bejder, 2006; Fessler & Holbrook, 2016). In dolphin synchronous surfacing, two males, but sometimes more, will surface to breathe side‐by‐side (<2 meters apart) synchronously (Connor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%